2015
DOI: 10.1002/pmic.201400586
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteome characterization reveals that Sendai virus infection activates mTOR signaling in human epithelial cells

Abstract: Sendai virus (SeV) is a common respiratory pathogen in mice, rats, and hamsters. Host cell recognition of SeV is mediated by pathogen recognition receptors, which recognize viral components and induce intracellular signal transduction pathways that activate the antiviral innate immune response. Viruses use host proteins to control the activities of signaling proteins and their downstream targets, and one of the most important host protein modifications regulated by viral infection is phosphorylation. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…cDNA microarray analyses on SeV‐infected cells indicated that the NF‐κB signaling pathway, IRF3 signaling pathway and IFN signaling pathway were activated by SeV infection . A phosphoproteomic analysis of SeV‐infected A549 cells highlighted that the mTOR (mechanistic target of rapamycin) signaling pathway plays a role in SeV infection process . Recently, Zhou et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cDNA microarray analyses on SeV‐infected cells indicated that the NF‐κB signaling pathway, IRF3 signaling pathway and IFN signaling pathway were activated by SeV infection . A phosphoproteomic analysis of SeV‐infected A549 cells highlighted that the mTOR (mechanistic target of rapamycin) signaling pathway plays a role in SeV infection process . Recently, Zhou et al.…”
Section: Discussionmentioning
confidence: 99%
“…cDNA microarray analyses on SeV-infected cells indicated that the NF-B signaling pathway, IRF3 signaling pathway and IFN signaling pathway were activated by SeV infection [14,28,29]. A phosphoproteomic analysis of SeV-infected A549 cells highlighted that the mTOR (mechanistic target of rapamycin) signaling pathway plays a role in SeV infection process [30]. Recently, Zhou et al performed a subcellular quantitative proteomics analysis on peroxisome-associated proteins in SeV-infected Hep G2 cells, and found 311 host proteins that were differentially regulated, among which they identified LGALS3BP and CALU as potential negative regulators of virus-induced IFN-I production [31].…”
Section: Discussionmentioning
confidence: 99%
“…In biomedicine, phosphoproteins are intriguing candidates for therapeutic interventions because the upstream kinases are relatively easy to target selectively with small molecule drugs (6). Previous MS-based phosphoproteome studies have shown major effects on host protein phosphorylation and reorganization of signal-transduction pathways in viral infections such as HIV-1 (7), lytic ␥ herpesvirus infection (8), porcine reproductive and respiratory syndrome virus (9), rift valley virus (10), Sendai virus (11), and human cytomegalovirus (12) infections.…”
mentioning
confidence: 99%
“…GO function annotation and enrichment analysis of the target genes according to three categories of biological process, cellular component, and molecular function demonstrated that viral infection might lead to a wide range of regulatory events in host system. Subsequently, KEGG pathway analysis of these putative target genes indicated involvement of Wnt signaling pathway, MAPK signaling pathway, TGF-beta signaling pathway, and mTOR signaling pathway, which have been shown to be important during the infection processes of some other viruses [5053]. The bioinformatic analysis described above provided a preliminary dataset for additional screening work to characterize the link between specific miRNAs and target genes during host responses to infection of HFMD-associated pathogens.…”
Section: Discussionmentioning
confidence: 99%